Cash management organisation decision-making: economics, strategy and operations - Wim Westerman (The Central European Review of Economics and Management (CEREM), 2020)
Aim: This article starts from the observations of two cash management experts, who witness varying company views on the almost-vanished issue of structuring the internal decision-making on the organisation of it. The aim of this article is to put the current challenging developments in a digitalizing world into a conceptual perspective. ~ Research design: The article singles out motives for either centralization or decentralization of cash management, models to organize cash management functions, as well as developments in the field over the last some thirty years. Various theoretical views are studied briefly in order to find a way out of the signalled paradox. ~ Findings: It can be concluded that multiple practices may coexist both within and between firms, whereby a refined understanding in terms of financial economics, strategic direction and operational flexibility is called for. ~ Originality: The present study is unique in that it is among the first to signal the return of the centralisation versus decentralisation issue in cash management in a rapidly evolving digital era and multi-legislation world. ~ Implications: The developments offer a unique opportunity for firms, further reducing their costs, to overthink their cash management system, including its relation to the external world. The study calls for follow-up research in terms of case studies at organisations with varying contingencies and survey questionnaires among representative samples.
Keywords: B27; G30; L23; 330; cash management organisation; (de-) centralisation; decision-making